A Study On Demand Of Handmade Products With Reference To Chennai, Tamilnadu. - et. al., Dr. Saikumari. V, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Handmade Products Have Its Own Market Spot In Our Country Where They Carry A Unique Expression. They Come Along With Our Culture And Heritage. Its Importance Is Felt Through Centuries And Now We Have The Support Of Government Through Programs In Order To Develop The Interest On Handmade Products. The Purpose Of This Study Is To Know The Preference Of Handmade Products Among Consumers. The Analysis From The Study Will Lend A Helping Hand To Retailers To Know Their Demand In Market Place. The Study Here Is Done Through Mail Survey And The Data Is Collected From The Age Group Of 18 - 50 Years. From This Population We Used Convenience Sampling Method To Collect Samples. Here We Intend To Do Descriptive Analysis With The Assistance Of Ms-Excel Software Where The Data Are Analysed Through Different Charts And Graphs.